2018
DOI: 10.1536/ihj.17-094
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of Left Atrial Appendage Diagnosed by Multimodality Imaging

Abstract: A 70-years-old male with a history of hypertension and drug resistant paroxysmal atrial fibrillation (AF) presented to our hospital for catheter ablation to his symptomatic AF. He had no prior surgical or percutaneous procedure to close or exclude the left atrial appendage (LAA). A transesophageal echocardiography (TEE) was performed to rule out intra-cardiac thrombus prior to the ablation procedure. Although the TEE imaging at multiple acquisition angles was obtained, the LAA could not be visualized and an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…All the patients were evaluated by an electrophysiologist in the outpatient clinic for eligibility, and all the participants signed a written consent form. Transesophageal echocardiography (TEE) was performed to assess LAA anatomy, and exclude LAA thrombus and significant structural cardiac abnormalities such as congenital absence 24) in all the patients within 1 week before the LAAC procedure. All the data were collected prospectively by means of a web-based database.…”
Section: Patient Selectionmentioning
confidence: 99%
“…All the patients were evaluated by an electrophysiologist in the outpatient clinic for eligibility, and all the participants signed a written consent form. Transesophageal echocardiography (TEE) was performed to assess LAA anatomy, and exclude LAA thrombus and significant structural cardiac abnormalities such as congenital absence 24) in all the patients within 1 week before the LAAC procedure. All the data were collected prospectively by means of a web-based database.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Enomoto Y et al diagnosed a case of an absent LAA and recorded no low-voltage areas or abnormal potentials around the usual root location of the LAA on 3-dimensional voltage mapping. 6 Absence of the LAA seems to be congenital according to existing reports. 2,6 The notable finding in our case that differentiates it from others is that we recorded abnormal potentials around the usual root location of the LAA using a 3-dimensional mapping system.…”
Section: Discussionmentioning
confidence: 91%
“…6 Absence of the LAA seems to be congenital according to existing reports. 2,6 The notable finding in our case that differentiates it from others is that we recorded abnormal potentials around the usual root location of the LAA using a 3-dimensional mapping system. In our case, voltage mapping indicated that there were large areas of low-voltage electrograms and scar tissue on the anterior wall.…”
Section: Discussionmentioning
confidence: 91%
“… 3 It has been previously postulated, though not proven, that congenital absence of LAA could infer a reduced thromboembolic risk similar to LAA occlusion. 4 However, limited outcome data or discussion of rudimentary appendages has been published. Given the uncertain thromboembolic risk associated with rudimentary LAA, anticoagulation decisions should be based on individual risk assessment.…”
mentioning
confidence: 99%